Topographic effects on vegetation greening and area expansion in global alpine zones under climate change - Linqing Zou; Feng Tian; Tianchen Liang; Rasmus Fensholt; Tao He; Gabriela Schaepman-Strub (International Journal of Applied Earth Observations and Geoinformation, 2025)
Alpine zones, located above the treeline in high mountain areas, are highly sensitive to global warming. Topography modulates land surface energy, mass and momentum fluxes and thus can largely influence vegetation growth under a warming climate. However, little is known about the topographical effects on vegetation changes during recent decades, especially in alpine vegetation at the global scale. Here we utilize 30 m spatial resolution Landsat imagery to quantify trends in vegetation greenness and vegetated areas during 1984–2023 in global alpine ecosystems and quantify the effects of topography on vegetation changes. Our results reveal that more than 99 % of the global alpine zones show concurrent significant (p < 0.05) vegetation greening and increasing vegetated areas. Yet, the effects of topography on the two vegetation metrics diverge in 85.49 % of the regions where the magnitude of the rate of vegetation greening decreases with higher elevation whereas the expansion rate of vegetated areas is faster with higher elevations. Moreover, vegetation dynamics also covary with the slope aspect, with polar-facing slopes experiencing higher trend magnitude in vegetation greenness (72.59 %) and vegetated areas (64.50 %) compared to the equatorial-facing slopes. Our findings provide a unified assessment of global alpine vegetation dynamics and highlight the complex impacts of topographic factors on alpine ecosystems under global climate change.